Law and ethics in nursing and healthcare - Avery, Graham (California SAGE Publishing, 2017)
A concise, highly accessible introduction to the key legal requirements needed to practice professionally within nursing and healthcare - a core element of the undergraduate nursing and healthcare curriculum. Each chapter supports theoretical learning with learning objectives, legislative case examples and practical scenarios.
The UK legal system-- An introduction to healthcare ethics-- Professional conduct-- Negligence-- Consent-- Mental health-- Deprivation of Liberty Safeguards-- Children-- Resource allocation-- Confidentiality-- End of life decisions-- Appendix.
Includes bibliographical references (pages [341]-354) and index.
Keywords: Law and ethics